2007
DOI: 10.1152/ajplung.00279.2005
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide 3-kinase, Src, and Akt modulate acute ventilation-induced vascular permeability increases in mouse lungs

Abstract: To determine the role of phosphoinositide 3-OH kinase (PI3K) pathways in the acute vascular permeability increase associated with ventilator-induced lung injury, we ventilated isolated perfused lungs and intact C57BL/6 mice with low and high peak inflation pressures (PIP). In isolated lungs, filtration coefficients ( Kf) increased significantly after ventilation at 30 cmH2O (high PIP) for successive periods of 15, 30 (4.1-fold), and 50 (5.4-fold) min. Pretreatment with 50 μM of the PI3K inhibitor, LY-294002, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
1
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 75 publications
(109 reference statements)
3
47
1
1
Order By: Relevance
“…(9). Of note, various reports have now identified augmented injury in animal models of both VILI and lipopolysaccharide-induced ALI associated with Akt inhibition (10,11) and we previously reported increased agonist-induced barrier disruption in Akt1-silenced EC monolayers (9). These findings suggest that Akt depletion contributes directly to the elaboration of acute inflammatory lung injury via increased lung vascular permeability.…”
Section: What This Study Adds To the Fieldsupporting
confidence: 51%
“…(9). Of note, various reports have now identified augmented injury in animal models of both VILI and lipopolysaccharide-induced ALI associated with Akt inhibition (10,11) and we previously reported increased agonist-induced barrier disruption in Akt1-silenced EC monolayers (9). These findings suggest that Akt depletion contributes directly to the elaboration of acute inflammatory lung injury via increased lung vascular permeability.…”
Section: What This Study Adds To the Fieldsupporting
confidence: 51%
“…13 Mechanical ventilation can increase Src phosphorylation by activating adherens junctions, Ca 2 þ entry through stretch-activated cation channels, deformation of cytoskeleton and integrins, focal adhesion kinases, G protein-coupled receptors, and growth factor receptors. 13 In the presence of active TGF-b1 and disrupted cell contacts of the bleomycin mouse model, integrin mediated Src activation after TGF-b1 signaling and Src inhibition blocked EMT and fibrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…13 Mechanical ventilation can increase Src phosphorylation by activating adherens junctions, Ca 2 þ entry through stretch-activated cation channels, deformation of cytoskeleton and integrins, focal adhesion kinases, G protein-coupled receptors, and growth factor receptors. 13 In the presence of active TGF-b1 and disrupted cell contacts of the bleomycin mouse model, integrin mediated Src activation after TGF-b1 signaling and Src inhibition blocked EMT and fibrogenesis. 34 Our results revealed that mechanical ventilation induced the phosphorylation of Src both in lung tissue and isolated myofibroblasts, which can be suppressed by Src knockout or pharmacologic inhibition with PP2, a selective Src kinase inhibitor remaining effective up to 6 h after ALI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations